2018
DOI: 10.1016/j.jjcc.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of E/e′ on ischemic stroke and atrial fibrillation in Japanese patients without atrial fibrillation

Abstract: E/e' was significantly associated with incidence of IS and new appearance of AF in non-AF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Furthermore, Arai et al demonstrated that an E/e' ratio >11 was an independent risk factor for new-onset AF. 21 In the present study, patients in the highest E/e' ratio quartile had a 2-fold higher prevalence of PAF than those in the lowest quartile ( Table 3).…”
Section: Sources Of Fundingsupporting
confidence: 47%
“…Furthermore, Arai et al demonstrated that an E/e' ratio >11 was an independent risk factor for new-onset AF. 21 In the present study, patients in the highest E/e' ratio quartile had a 2-fold higher prevalence of PAF than those in the lowest quartile ( Table 3).…”
Section: Sources Of Fundingsupporting
confidence: 47%
“…E/e' is commonly used as a surrogate of LV filling pressure [16] and reflects the severity of heart failure [30] . Blood pressure is maintained in patients with a high E/e' with a negative fluid balance by administration of furosemide or continuous hemofiltration [31] .…”
Section: Post-induction Hypotension In Patients With Cardiovascular D...mentioning
confidence: 99%
“…These patients were referred for a comprehensive cardiovascular evaluation by their general practitioners thus reflecting a primary care setting. The clinical question was to assess whether the available evidence reported in multiple, different experimental settings [1][2][3][4][19][20][21] may be duplicated in the heterogeneous clinical scenario encountered in every day clinical practice. During a midterm follow-up, e' and E/e' were both associated with clinical outcome in these patients, but only e' maintained its independent prognostic information in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…When used in conjunction with mitral peak early filling velocity (E), the E/e' ratio is a widely used noninvasive estimate of LV filling pressure (LVFP) that plays a pivotal role in evaluating diastolic dysfunction [5]. Although the prognostic value of E/e' is established, a number of studies have raised concerns about its diagnostic accuracy in various cardiovascular conditions [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%